2018
DOI: 10.1038/s41419-017-0230-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 2 promotes human trophoblast cell invasion by upregulating N-cadherin via non-canonical SMAD2/3 signaling

Abstract: BMP2 expression is spatiotemporally correlated with embryo implantation and is crucial for endometrial decidualization and fertility in mice. BMP2 has been reported to increase the mesenchymal adhesion molecule N-cadherin and enhance cell invasion in cancer cells; moreover, studies suggest that N-cadherin promotes placental trophoblast invasion. However, whether BMP2 can promote trophoblast cell invasion during placentation remains unknown. The objective of our study was to investigate the effects of BMP2 on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 39 publications
7
48
0
Order By: Relevance
“…We have previously shown that BMP2 promotes human trophoblast invasion by upregulating N-cadherin expression and activin A production. 14,15 Here we further demonstrate that ID1 is involved in BMP2-induced trophoblast invasion. However, others have shown that Id1 is downregulated during the differentiation of rat Rcho-1 choriocarcinoma cells into trophoblast giant cells, which are thought to be somewhat equivalent to human EVTs.…”
Section: F I G U R E 4 Knockdown Of Id1 or Igfbp3 Abolishes Bmp2-indusupporting
confidence: 60%
See 2 more Smart Citations
“…We have previously shown that BMP2 promotes human trophoblast invasion by upregulating N-cadherin expression and activin A production. 14,15 Here we further demonstrate that ID1 is involved in BMP2-induced trophoblast invasion. However, others have shown that Id1 is downregulated during the differentiation of rat Rcho-1 choriocarcinoma cells into trophoblast giant cells, which are thought to be somewhat equivalent to human EVTs.…”
Section: F I G U R E 4 Knockdown Of Id1 or Igfbp3 Abolishes Bmp2-indusupporting
confidence: 60%
“…As the biggest subfamily of the TGF‐β superfamily, bone morphogenetic proteins (BMPs) are essential for placental development . Expressed at the maternal‐fetal interface, BMP2 plays essential roles in endometrial decidualization and EVT cell invasion . In addition, embryo implantation promotes endometrium decidualization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…egEVTs invade the endometrial glands to facilitate histiotrophic nutrition to the embryo, while evEVTs transform endometrial spiral arteries and decrease their resistance to establish the uteroplacental circulation . The molecules that mediate trophoblast invasion of the decidua are cell adhesion molecules (CAMs) like integrins, cadherins and fibronectin, metalloproteinases (MMPs), and tissue inhibitors of metalloproteinases (TIMPs). During trophoblast invasion of the decidua, the EVT firstly migrates and degrades the endometrial extracellular matrix with the aid of the MMPs .…”
Section: Introductionmentioning
confidence: 99%
“…BMP2 induces human TB cell invasion by upregulating activin A and inhibin A. BMP2 initiates both canonical SMAD1/5/8 via the ALK3 receptor and non-canonical SMAD2/3 pathways [46]. The same group extended these studies and showed that BMP2 promotes TB cell invasion by upregulating N-cadherin via non-canonical ALK2/3/4-SMAD2/3-SMAD4 signaling [78]. They also revealed the role of BMP2 in promoting TB invasion and tube-like formation by ID1-mediated insulin-like growth factor binding protein-3 (IGFBP3) upregulation in primary and HTR8/SVneo cell cultures [47].…”
Section: Bmp Cascadementioning
confidence: 92%